Role of Fine Needle Aspiration Cytology (FNAC) in the Daignosis of Thyroid Swellings - Ullah, Safir; Mumtaz, Naeem; Khan, Akbar (Journal of Postgraduate Medical Institute, 2011)
This study was conducted to know the validity of FNAC in the diagnosis of thyroid swellings. Total 300 cases were included in this study. All had FNAC examination as out patient procedure. Out of 300 cases, 285 were operated and specimen were sent for histopathology. Full clinical data of every patient was recovered. FNAC is safe, inexpensive and less invasive diagnostic modality with excellent patient compliance. its routine use can make the management of thyroid swellings cost effective by avoiding unnecessary operation on conditions like simple cysts and thyroiditis. FNAC has higher accuracy (94.2% sensitivity and 94% specificity) in case of diagnosis of maligmant thyroid disease.